Slugs (of Florida) (Gastropoda: Pulmonata) - Lionel A. Stange; Jane E. Deisler (EDIS, 2005)
Florida has a depauparate slug fauna, having only three native species which belong to three different families. Eleven species of exotic slugs have been intercepted by USDA and DPI quarantine inspectors, but only one is known to be established. This document is EENY-087 (originally published as DPI Entomology Circulars No. 197 and 261), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: June 1999. Revised: April 2004.